Ecofisiologia da regeneração de espécies espontâneas do banco de sementes do solo em campo nativo submetido a diferentes sistemas de cultivo - Ferreira, Otoniel Geter Lauz (2006)
Soil seed bank spontaneous species regeneration dynamics of a previously cultivated native grassland, under different systems, was evaluated in five cropping seasons (May/2002, 2003 and October/2002, 2003, 2004). Three soil cultivation systems were compared: no tillage, minimum tillage and conventional tillage along with three cropping rotation sequences: soybean/corn in Summer (alternating wheat and oats for grain in Winter), soybean/oats + common vetch/corn and soybean/corn, alternating with Winter fallow. Number of species and vegetation structure (Braun- Blanquet scale) were evaluated by uni and multivariate analyses. Cultivations with low soil mobilization and fallow in cropping sequences determined a greater number of regenerated species from soil seed bank. No tillage system favored the appearance of perennial species and greater probability of native grassland species regeneration. Regeneration of spontaneous species from seed bank of a previously cultivated native grassland, managed under different systems, showed seasonal pattern, with alterations upon increasing number of cultivations. Cropping sequences affected autumnal vegetation but they were not determinant in the occurrence of native grassland species.